The Role of Signals in Online Auction Purchase Decisions - Cypryjański Jacek; Grzesiuk Aleksandra (Folia Oeconomica Stetinensia, 2015)
There is a growing interest in behavioural economics contradicting the empirical prediction of rational choice theory once applied to online auctions. The issue is of particular relevance due to the large use of online auctions and the anticipated growth in the future. Online auctions combine the conventional auction model with information technology. However, information asymmetry within such auctions causes risks and uncertainties that influence consumer purchase intentions. The research investigates online consumers’ behaviour. The Authors suggest that due to the high perceived risk of the online buying process consumers are prompted to use cues of seller’ reputation. In a series of six experiments conducted via the auction site Allegro.pl in Poland a number of signals from auction web pages has been manipulated to influence purchase intention. The results suggest that several signals can be used to stimulate online customers’ behaviour. The results of these experiments indicate that buyers are more susceptible to the influence of “visual” signals than signals that require greater involvement of the buyer (to read information). The conducted experiments contribute to a more comprehensive understanding of online auction users’ behaviour. And finally it provides some managerial implications to increase online auction effectiveness from the seller’s perspective.